2021
DOI: 10.29333/iji.2021.14425a
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Transformational Leadership Strengthening, Self Efficacy, and Job Satisfaction to Increase Teacher Commitment

Abstract: Based on the problem that the teacher's commitment to the profession is still not as expected, this study aims to find ways to improve teacher commitment to the profession by examining the influence of transformational leadership, self-efficacy, and job satisfaction. The methodologies used are the Path method and Sitorem method. The study population was 1307 Non-Civil Servant, middle school teachers in Cirebon District, Indonesia with a research sample of 136 teachers. The Non-Civil Servant middle school teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
(11 reference statements)
2
17
0
5
Order By: Relevance
“…According to some recent studies (Botella et al, 2019;Dicke et al, 2019;El-Hout et al, 2021), gender roles and social expectations of occupation will impact the decision-making processes, the determination(s) of the participants in this study was strong enough to overcome the challenges. In summary, the participants' personal voices followed and echoed the finding from the finding of a project (Falco & Summers, 2019), advocating that the significant childhood experiences and having the self-efficacy in individuals interests and academic courses can significantly influence and increase the likelihood of enrolling an academic programme and career pathway after their academic voyage (Setyaningsih & Sunaryo, 2021). In line with the Social Cognitive Career and Motivation Theory (Dos Santos, 2021aSantos, , 2021bKwee, 2021), the results found that when individuals' academic and school interests in the STEM courses were based on former childhood experiences and suggestions from third parties, that could influence their motivations, career decisions, and sense-making processes.…”
Section: Discussionmentioning
confidence: 93%
“…According to some recent studies (Botella et al, 2019;Dicke et al, 2019;El-Hout et al, 2021), gender roles and social expectations of occupation will impact the decision-making processes, the determination(s) of the participants in this study was strong enough to overcome the challenges. In summary, the participants' personal voices followed and echoed the finding from the finding of a project (Falco & Summers, 2019), advocating that the significant childhood experiences and having the self-efficacy in individuals interests and academic courses can significantly influence and increase the likelihood of enrolling an academic programme and career pathway after their academic voyage (Setyaningsih & Sunaryo, 2021). In line with the Social Cognitive Career and Motivation Theory (Dos Santos, 2021aSantos, , 2021bKwee, 2021), the results found that when individuals' academic and school interests in the STEM courses were based on former childhood experiences and suggestions from third parties, that could influence their motivations, career decisions, and sense-making processes.…”
Section: Discussionmentioning
confidence: 93%
“…Low academic self-efficacy will appear in situations that suppress students' emotional condition (Sudirman et al, 2020). It is vital to provide suitable learning settings to promote self-efficacy to develop career International Journal of Instruction, July 2022 • Vol.15, No.3 orientation in students (Kotova et al, 2021;Sides & Cuevas, 2020) and produce more professional competences (Dos Santos, 2020;Dwiretno & Setyarsih, 2018;Setyaningsih & Sunaryo, 2021). Educators are also required to provide learning resources such as student activity sheets to aid promote thinking orientation (Suhirman et al, 2021).…”
Section: The Practicality Of Rqanimentioning
confidence: 99%
“…However as a result, many factors influence teacher commitment such as school leader leadership, school climate, teacher workload, teacher attitude, and student discipline (Kasa et al, 2020;Lela et al, 2020;Mustafa et al, 2019). Successful leaders are usually able to increase teacher engagement in their schools (Don et al, 2021;Setyaningsih & Sunaryo, 2021). This quality of leadership becomes a measure because imperial studies show that wise school leaders are capable of producing committed teachers (Amhag et International Journal of Instruction, July 2022• Vol.15, No.3 al., 2019Raman & Shariff, 2017).…”
Section: Research Backgroundmentioning
confidence: 99%